A simply effective double-coating cathode with MnO2 nanosheets/graphene as functionalized interlayer for high performance lithium-sulfur batteries. (20th July 2016) - Sun, Wang; Ou, Xianguo; Yue, Xinyang; Yang, Yuxiang; Wang, Zhenhua; Rooney, David; Sun, Kening
Graphical abstract: MnO2 nanosheets grown on the surface of highly conductive graphene resulted in a coupled composite bilayer electrode when coated onto a sulfur cathode. In this way, a high initial specific capacity of 1395 mA h g −1 at a rate of 0.5 C, a Coulombic efficiency approaching 100 % and steady cyclic efficiency with a fade rate of 0.3% per cycle from 10 to 100 cycles has been achieved. Highlights: An simply effective double-coating cathode is designed for Li-S battery. This cathode exhibits high capacity and steady cyclability. MnO2 nanosheets/graphene functionalized interlayer bound soluble polysulfide. A novelty mechanism is proposed to explain the enhanced performance during cycling Abstract: Herein, we report a facile and effective adsorption strategy to improve the performance of Lithium-Sulfur (Li-S) batteries. MnO2 nanosheets grown on the surface of highly conductive graphene resulted in a coupled composite bilayer electrode when coated onto a sulfur cathode. In this way, a high initial specific capacity of 1395 mA h g −1 at a rate of 0.5C, a coulombic efficiency approaching 100% and steady cyclic efficiency with a fade rate of 0.3% per cycle from 10 to 100 cycles has been achieved. This hybrid electrode not only shows enhanced electrochemical performance but can also be easily controlled and scaled thereby aiding future commercialization of high-performance Li-S batteries.